Practitioner Profile: Lindsay Bryan-Podvin (Journal of Financial Therapy, 2019)
Lindsay Bryan-Podvin, owner and founder of Mind Money Balance, is a financial therapist who started her career in the field of mental health treatment and advocacy. She specializes in working with heterosexual couples with breadwinning women.
Keywords: financial therapy; financial therapy practice